2019
DOI: 10.1097/j.pain.0000000000001483
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in central nervous system plasticity and pain in experimental autoimmune encephalomyelitis

Abstract: Multiple sclerosis (MS) is a neurodegenerative autoimmune disease with many known structural and functional changes in the central nervous system. A well-recognized, but poorly understood, complication of MS is chronic pain. Little is known regarding the influence of sex on the development and maintenance of MS-related pain. This is important to consider, as MS is a predominantly female disease. Using the experimental autoimmune encephalomyelitis (EAE) mouse model of MS, we demonstrate sex differences in measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 49 publications
4
12
0
1
Order By: Relevance
“…Whereas microglia were required for pain development in male mice, adaptive immune cells, like T cells mediated hypersensitivity in females (Sorge et al, 2015). Similar, a recent study proposed that tactile hypersensitivity in female EAE mice may be more immune-driven, whereas pain in male mice with EAE may rely more heavily on neurodegenerative and plasticity-related mechanisms (Catuneanu et al, 2019). This is in line with our data indicating that blocking T cell mediated neuroinflammation is therapeutic on female pain.…”
Section: Discussionsupporting
confidence: 91%
“…Whereas microglia were required for pain development in male mice, adaptive immune cells, like T cells mediated hypersensitivity in females (Sorge et al, 2015). Similar, a recent study proposed that tactile hypersensitivity in female EAE mice may be more immune-driven, whereas pain in male mice with EAE may rely more heavily on neurodegenerative and plasticity-related mechanisms (Catuneanu et al, 2019). This is in line with our data indicating that blocking T cell mediated neuroinflammation is therapeutic on female pain.…”
Section: Discussionsupporting
confidence: 91%
“…To detect a transcriptional signature within the DRG of EAE mice, we performed next-generation sequencing (NGS) of DRGs taken from mice at the onset of the disease when pain hypersensitivity is evident [2, 3, 20]. Roughly 20,000 genes were detected by sequencing.…”
Section: Resultsmentioning
confidence: 99%
“…Experimental autoimmune encephalomyelitis (EAE) is a mouse model used to study the pathophysiology of MS, where an autoimmune response is artificially induced against the myelin of the central nervous system (CNS). The model produces immune-related demyelination of the CNS [24]. People with MS experience altered motor function but recent estimates report that 63% of people living with MS are additionally negatively impacted by disturbances to sensation such as chronic, neuropathic pain [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, Swing Time , which is essentially the same as Swing Duration , was found to be increased in both experimental cohorts and the difference was verified by two independent observers. Of note, it has been shown that Swing Duration increases with pain [57,58,59], and pain, which is a frequent and disabling symptom in MS patients, as well characterizes EAE animals to some extent [60]. Of note, a recent study showed that pain can as well be observed during the pre-clinical EAE phase [61].…”
Section: Discussionmentioning
confidence: 99%